Physical properties of root cementum: Part 12. The incidence of physiologic root resorption on unerupted third molars and its comparison with orthodontically treated premolars: A microcomputed-tomography study - Deane, Sheryn; Jones, Allan S.; Petocz, Peter; Darendeliler, M. Ali (American journal of orthodontics and dentofacial orthopedics, 2009)
Root resorption can occur as a physiologic or a pathologic process, and it is an unwanted side effect of orthodontic treatment. No baseline studies have assessed this phenomenon in the absence of force variables such as mastication, parafunction, and soft-tissue pressure. In this study, we investigated the incidence and quantitative value of root resorption on unerupted third molars with normal development using microcomputed tomography. Nine unerupted, nonimpacted maxillary third molars were collected from 6 patients (ages, 19.47 ± 1.89 years). The teeth were examined with microcomputed tomography and compared with teeth from other studies. (The other teeth had been treated with buccally directed light [25 g] or heavy [225 g] forces applied for 28 days, or light [25 g] or heavy [225 g] intrusion forces for 28 days.) Imaging and volumetric analyses showed resorption craters in many locations and with various magnitudes. Analysis of variance was completed by position ( P = 0.04), surface ( P = 0.07), height ( P = 0.045), left or right side of the mouth ( P = 0.85), and subject ( P = 0.70). The midroot region on the mesial surfaces of the third molars, near the root structure of adjacent erupted second molars, had the greatest statistical significance. When compared with crater volumes of fully erupted first premolars, we found that the unerupted third molar sample had a slightly greater cube root volume per tooth than the erupted first premolars not subjected to orthodontic force and a similar cube root volume per tooth as did first premolars subjected to light (25 g) buccal and intrusive orthodontic forces. Root resorption as a consequence of orthodontic treatment might be added to a baseline level of root resorption. The elevated results suggest that resorption might occur as part of hard-tissue remodeling and turnover, eruption, or transmission of masticatory forces through the dentition to the alveolar bone.